Narrating the Whale: Rescue, Compassion, and Sacred Waterscapes in Coastal Vietnam - Huy Binh Nguyen; Chi P Pham (The English Department, Faculty of Humanities & Creative Industries, Petra Christian University, 2026)
This article argues that Vietnamese and Cham whale narratives articulate a distinctly coastal multispecies ethics in which whales are not merely symbols of nature or residual spirits, but moral beings embedded in relations of rescue, obligation, and mourning. Drawing on ethnographic and historical accounts of Cá Ông [Whale God] and Po Riyak [God of the Waves] among ethnic communities in Vietnam, this article examines how whale worship embodies ethical frameworks that shape human conduct toward the sea and its more-than-human inhabitants. A comparative analysis shows that Vietnamese and Cham traditions demonstrate distinct yet overlapping ethical regimes in which whales function as protectors and oceanic mediators whose deaths demand ritual recognition. It further suggests that coastal Vietnam offers an alternative ethical imagination grounded not in mastery over nature, but in vulnerability, gratitude, and interspecies responsibility. The article presents an ocean-centered perspective on Southeast Asia within the fields of multispecies studies and environmental humanities, emphasizing its importance in the context of the current ecological crisis - particularly marine environmental degradation, plastic pollution, and industrial fishing - issues that are reshaping and challenging coastal ethical systems.